Responses of selected metabolites in Moringa oleifera Lam. leaves to seasonal variations - Ralepele, Floyd Maseye (My University, 2020)
Moringa oleifera Lam.is significant in the livelihood of many populations in the tropics and subtropics region. It was discovered centuries ago in India and has since become one of the most popular medicinal plants due to its therapeutic and nutritional properties. The high antioxidant activity in M. oleifera has highlighted the phytochemical compounds that are attributed to the medicinal and nutritional benefits. The species is regarded as the ‘Miracle tree’ and its cultivation is thus essential due to the potential in providing the necessary essential nutrients and herbal compounds. Due to climate change, environmental conditions are gradually changing in all climatic seasons, and as a result, the warmer and cooler seasons are exhibiting signs of extreme conditions. Hence, a research study on the responses of secondary metabolites in medicinal plants to seasonal variation is needed to assess the impact of these stress conditions on the pathways of the phytochemical production. Therefore, the present study was aimed at investigating the responses of selected secondary metabolites in the M. oleifera leaves to South African calendar-based seasons (summer, autumn, winter, and spring) from March 2018 to February 2019. The leaf samples were collected from a research farm at Hammanskraal, Pretoria (Gauteng province, South Africa). The quantification of the selected bioactive compounds was performed by UV-VIS spectrophotometry and UHPLC-DAD-qTOF-MS. In addition, 2,2-diphenyl-β-picrylhydrazyl assay and leaf morphology were used to investigate the anti-oxidant activity of the extract and plant leaf colour changes, respectively. The results from the leaf morphology have shown that Moringa oleifera Lam. has the potential to adapt under chilling temperatures however the plant has also shown high sensitivity to extremely cold temperatures and consequently becomes dormant under such conditions, particularly during the last two months of the winter season (July and August). As a result, the leaf sample collection for the winter season was performed only in the first month of winter (June) as well as in the last two months of spring (October and November for spring collection) for the phytochemical analysis. Interestingly, the species remains evergreen during all the seasons in its native regions such as Northern India. However, it has shown to be deciduous in South Africa, particularly in the Hammaskraal region. The phytochemical results showed a gradual increase in the total phenolic and flavonoid content during autumn (4123±1516.97mg GAE/100g and 1097.29±55.18 mg QE/100g, respectively) which later decreased in winter (3467.85±175,11mg GAE/ 100g and 439.10±12.29mg QE/100g, respectively) as compared with the spring and summer seasons. Total phenolic content increased to an average of 1253.59±258.34 mg GAE/100g during the last two months of spring and 3889.61±389.64 mg GAE/100g in summer. Similarly, the total flavonoid content increased during the last two months of spring and decreased in summer with an average of 734.14±38.10 mg QE/100g and 322.25±53.74 mg QE/100g, respectively. Quercetin and kaempferol content remained fairly constant with slight fluctuations in autumn and summer. However, Quercetin content remained constantly higher (258.11±73.47mg/100g) as compared to the kaempferol content (13.47±5.73 mg/100g). The antioxidant activity in M. oleifera leaves was significantly high in the winter and summer seasons. This response was indicated by low EC50 values of 1.61±0.18 mg/mL in winter and 1.98±0.23 mg/mL in summer. This data correlates with total phenolic and total flavonoid content, particularly in summer. On the contrary, the EC50 high values indicated lower antioxidant activity during autumn (2.049±0.13 mg/mL) and spring (4.03±0.57 mg/mL). The data obtained from the current study, illustrated the impact of seasonal variations on the selected metabolites and antioxidant activity in Moringa oleifera Lam. leaves. It may be concluded that the species exhibited great sensitivity to the winter season by demonstrating a state of dormancy and subsequent abscission. Furthermore, the high antioxidant activity in the first month of winter and the entire summer season indicated possible oxidative stress that the species was eradicating by potentially increasing the total phenolic and flavonoid content. The present study serves as a meaningful contribution towards the farming, harvesting and ultimate consumption of Moringa oleifera Lam.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2020